Knowledge Equivalence Discourse in New Zealand Secondary School Science - Rata, Elizabeth; Taylor, Anita (New Zealand journal of educational studies, 2015)
The theoretical inquiry undertaken in this paper examines the discourse of knowledge equivalence used to justify conflating academic and non-academic subjects in New Zealand secondary school science. The purpose is to open up a critical discussion of the discourse and its influence on curriculum and pedagogy. Using a conceptual methodology, we identify the differences between academic and non-academic subjects to argue that there are sound epistemological and equity reasons not to combine academic and non-academic subjects into innovated pathways. A research study which explored the curriculum practices of several senior science teachers is used to illustrate our theoretically derived analysis and explanation of the knowledge equivalence discourse.